Fetal Growth Charts For Normal Pregnant Women Of Saudi Arabia - Al-Marri, Hana Mohammed Salem (2020)
This study aimed to create new reference ranges for fetal biometric parameters in the Saudi Arabian population. Overall, 4075 pregnant women who visited the Maternity and Children Hospital (Dammam, Saudi Arabia) and King Fahd University Hospital (Al Khobar, Saudi Arabia) were enrolled retrospectively during 2013–2015. Based on the records at the Record Units of both hospitals, the data including ultrasound (US) findings using Voluson E6 (GE Healthcare, Austria) and Medison US SonoAce R5 system, with a 2–5 MHz abdominal probe [namely crown–rump length (CRL), biparietal diameter (BPD), femur length (FL), abdominal circumference (AC), head circumference (HC), occipitofrontal diameter (OFD), and estimate fetal weight (EFW)] from 6th to 13th week of gestational age (GA) for CRL and from 12 weeks for BPD, 20 weeks for HC and EFW, 13 weeks for FL, 17 weeks for OFD,15 weeks for AC to 41st weeks of GA. The antenatal care (ANC) parameters [namely blood pressure (BP) used Model CARESCAPE V100 Monitor and Sun Tech CT40, hemoglobin (Hb)] were recorded from 6th to 41st week of GA. Statistical analyses comprised frequency analysis, descriptive statistics, mean comparison, regression analysis, and paired sample t-test was performed by using SPSS software version 22.0. Mean participant age was 29  6 years. Furthermore, the analysis of maternal blood pressure during pregnancy illustrated that approximately one-third of diastolic blood pressure values were in the pre-high range (80–90 mm/Hg). Most participants were diagnosed with anemia during their pregnancy (51.16%) and postpartum (80.36%).